Talking the Talk vs. Walking the Walk: Salience of Information Needs in Querying vs. Browsing - Bilenko, Misha; White, Ryen W.; Richardson, Matthew; Murray, G. Craig (31st Annual International ACM SIGIR Conference on Research and Development in Information Retrieval (SIGIR 2008), Singapore, 2008)
Traditional information retrieval models assume that users express their information needs via text queries (i.e., their “talk”). In this poster, we consider Web browsing behavior outside of interactions with retrieval systems (i.e., users’ “walk”) as an alternative source of signal describing users’ information needs, and compare it to the query-expressed information needs on a large dataset. Our findings demonstrate that information needs expressed in different behavior modalities are largely non-overlapping, and that past behavior in each modality is the most accurate predictor of future behavior in that modality. Results also show that browsing data provides a stronger source of signal than search queries due to its greater volume, which explains previous work that has found implicit behavioral data to be a valuable source of information for user modeling and personalization.